2013
DOI: 10.1016/j.otsr.2013.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Axial MRI index of patellar engagement: A new method to assess patellar instability

Abstract: AEI is a new index to measure LPD. It can be obtained in all cases because it is obtained from two different MRI views. The normal value is close to 1. It can be used to measure patellar instability on the axial plane in patients with OPI, especially in the most severe cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
7

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 23 publications
1
29
0
7
Order By: Relevance
“…Within the control group, four of five data sets do not cross the mean of the combined control group. The study by Guilbert et al 15 has the largest cohort (n=180) in the control and PFI groups. Their PFI group has no values crossing the traditional threshold of pathological lateral patella tilt, that is, 20°.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Within the control group, four of five data sets do not cross the mean of the combined control group. The study by Guilbert et al 15 has the largest cohort (n=180) in the control and PFI groups. Their PFI group has no values crossing the traditional threshold of pathological lateral patella tilt, that is, 20°.…”
Section: Discussionmentioning
confidence: 99%
“…For the TT-TG distance, 16 studies were excluded for either using the tibial tubercle as an osseous landmark (5 studies),18 30–33 or no clear description of measurement parameters reported (11 studies) 9–11 14 15 27 34–38…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Described by Guilbert et al , the PF AEI represents the percentage of the patellar cartilage that is actually engaged in the trochlear cartilage measured on a patellar and a trochlear axial cut using a line tangent to the posterior femoral condyles as reference (figure 3A). 13 The normal value is close to 1.…”
Section: Methodsmentioning
confidence: 83%
“…7b): 15 this is a new index of measurement for lateral patellar displacement and is a direct reflection of this entity. Measurement of AEI can be obtained with two different axial MRI views, using the cartilaginous and posterior condylar landmarks as references.…”
Section: Evaluation Of Dysplasiamentioning
confidence: 99%